Properties of body composition of female representatives of the Polish national fencing team – the sabre event - Jagiełło, Władysław; Marina, Jagiełło; Maciej, Kalina Roman; Jan, Barczyński Bartłomiej; Artur, Litwiniuk; Jarosław, Klimczak (Biology of Sport, 2017)
Fencing is a combat sport whose form of direct confrontation involves hitting the opponent with a weapon. The purpose of the study was to determine the properties of body composition of female representatives of the Polish national fencing team. The study involved 11 female athletes of the Polish national fencing team. Their age was 16-22 years (19±2.32), body weight 52-78 kg (59.7±7.4), body height 158-183 cm (167.46±6.10) and the training experience 7.64±3.47 years. The reference group consisted of 153 students of Warsaw University of Technology (Poland). Twenty basic somatic characteristics were measured. The following indices were calculated: slenderness, Rohrer’s, BMI, Manouvrier’s, and pelvic-shoulder indices. Density of the body, total body fat, active tissue, the overall profile of body composition and internal proportions of the body were determined. Analysis of internal proportions of factors of the athletes’ body composition revealed significant differences in particular groups of features. The total size of the athletes’ bodies is due to less-than-average magnitude of the length and stoutness characteristics and a high magnitude of adiposity (M = 0.63) in the Polish female national team of fencers (sabre) calculated from the normalized values for the control group. The proportions of features within the analysed factors revealed a significant advantage of the length of the upper extremity over the lower one and a distinct advantage of forearm musculature. The specific profile of body composition of female athletes practising sabre fencing is most likely due to long-term effects of training as well as the system of selection of persons with specific somatic prerequisites developed in the course of many years of training practice.